2007
DOI: 10.1016/j.clinbiomech.2007.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding from the bone marrow enhances remodeling of the in situ frozen-thawed anterior cruciate ligament

Abstract: Introduction. The purpose of this study is to biomechanically and histologically evaluate the effect of bleeding from bone marrow on remodeling of the in situ frozen-thawed anterior cruciate ligament.Methods. Forty-four rabbits were used. Eight rabbits were used to evaluate the amount of bleeding at days 1-4. Thirty-six rabbits were divided into 2 groups, after the right anterior cruciate ligament underwent the freeze-thaw treatment. In Group I, no treatments were applied. In Group II, a tunnel was drilled int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Other authors have also noted the high healing potential of small tears and particularly lateral tears left untreated at the time of ACLR. 36,43 In animal models, blood clot from ACLR bone tunnels influences graft healing, 44 and Bab and Einhorn 3 reported that multiple growth factors are present within bone marrow-derived clot-including platelet-derived growth factor. Galliera et al 13 demonstrated elevated postoperative levels of vascular endothelial growth factor (VEGF) and VEGF receptor 2 after ACLR compared with arthroscopic partial meniscectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have also noted the high healing potential of small tears and particularly lateral tears left untreated at the time of ACLR. 36,43 In animal models, blood clot from ACLR bone tunnels influences graft healing, 44 and Bab and Einhorn 3 reported that multiple growth factors are present within bone marrow-derived clot-including platelet-derived growth factor. Galliera et al 13 demonstrated elevated postoperative levels of vascular endothelial growth factor (VEGF) and VEGF receptor 2 after ACLR compared with arthroscopic partial meniscectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Basing our study on this observation, we suggest that the occurrence of hematoma and bleeding from the bone marrow even during ACL reconstruction enhances the healing of the lateral meniscus tear. Yasuda et al 39 demonstrated that bleeding from the bone marrow after creating bone tunnels plays an important role in graft remodeling. The blood clot from a bone tunnel contains various types of cells and various growth factors.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the observed increased incidence of LMRA in chronic cases, one may question whether the avulsion occurred at the time of the ACL injury and did not heal or whether it occurred later, as a result of laxity associated with ACL insufficiency. Untreated radial or longitudinal tears of the posterior horn of the lateral meniscus appear to have a higher chance of healing than medial meniscus tears [ 10 15 ] for several reasons: there is better blood supply to the posterior horn of the lateral meniscus in comparison to the pars intermedia [ 16 ]; concomitant ACL reconstruction also promotes healing as a result of intraarticular blood clotting [ 17 , 18 ]; and increased joint stability may reduce forces on the lesion, enhancing the chances of spontaneous healing. Shelbourne and Heinrich [ 13 ] reported that stable radial flap tears and peripheral posterior horn tears that did not extend more than 1 cm anterior to the popliteus tendon could be treated successfully by leaving them in situ.…”
Section: Discussionmentioning
confidence: 99%